Die sentrale plek van ’n lewensen wêreldbeskouing - Strauss, D. F. M. (Koers, 2010)
The central place of a life- and worldview While taking into account the difference between a worldview and a lifeview this article focuses on the important foundational role of a life- and worldview – precisely because Professor Bennie van der Walt dedicated so much of his scholarly output to the implications of the Christian world- and lifeview. Within the latter context we find an important pillar safeguarding us against a biblicistic (or fundamentalist) misapprehension of the scope of the biblical message. God’s law-Word for being a creature must be distinguished from the written Word which refers us to the former. An important outcome of the Christian life- and worldview is particularly found in the ideal of Christian scholarship – a theme with which Professor Bennie van der Walt continuously occupied himself. Because the after-effect of the Roman Catholic split of reality – in a sacred supernatural and a natural “secular” sphere – with the accompanying oppositions (such as church and world, faith and reason, sacred and secular, soul and body, and so on) – is still found within our protestant legacy, the rest of this article focuses on a perspective that can help us to transcend this dichotomy. The basic conception is that the directional antithesis between good and evil (redemption and sin) ought not to be twisted into a structural opposition within the good creational order of God for creatures.